Shale rocks of the Spassk suite of the Lower Cretaceous as the prospective objects for extracting hydrocarbons - V.S. Bodnarchuk, A.P. Mazur (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
In connection with opportunities for extracting hydrocarbons from the condensing shale rocks there appears the necessity for a detailed research, especially in the territory of Ukraine. Previously, these strata were considered only as oil and source rocks. At present, it has been proved in the world that deposits enriched in organic matter can be both source and reservoir rocks. In the Western region of Ukraine the black shale rocks of the Oligocene Menilite suite and the Spassk suite of the Lower Cretaceous are the most enriched in organic matter. These sediments are most common within the Inner zone of the Precarpathian foredeep (the Menilite suite), the Skybova zone of the Carpathians (the Menilite and Spassk suites) and the Krosno zone (the Spassk suite). This work is focused on the Spassk suite of the Lower Cretaceous, which lies within the Krosno zone, its detailed location, lithological and petrographic features. A thorough description of the mineral composition of the finished rock sections is provided. The carboniferous organic matter of the black shale rocks of the Spassk suite is described in detail. All other important mineral inclusions of prospective rocks, which occurred in finished rock sections within the studied regions, are characterized. The material, submitted in the article, is the basis for the continuation of thorough geological and geophysical researches within the selected perspective areas, and also the future possible production of industrial gas hydrocarbons.